Foliar spray of B+Fe to mitigate the heat and moisture stress in late sown lentil crop in new alluvial zone of West Bengal - Kumari, V Visha; Nath, Rajib; Gupta, Kajal Sen; M A, Sarath Chandran (Indian Farming, 2022)
The study revealed that spraying micronutrients especially a mixture of B + Fe @ 0.5% and B + Zn + Fe @ 0.5% are equally effective in mitigating terminal heat and drought stress. However, the increase in growth and yield attributes might lead to competition among the flowers and thus reduce the pod yield in the case of B + Zn + Fe @ 0.5%.